Estrogen receptor α is required for oviductal transport of embryos. Issue 4 (12th January 2017) - Li, Shuai; O'Neill, Sofia R. S.; Zhang, Yong; Holtzman, Michael J.; Takemaru, Ken‐Ichi; Korach, Kenneth S.; Winuthayanon, Wipawee
Abstract : Newly fertilized embryos spend the first few days within the oviduct and are transported to the uterus, where they implant onto the uterine wall. An implantation of the embryo before reaching the uterus could result in ectopic pregnancy and lead to maternal death. Estrogen is necessary for embryo transport in mammals; however, the mechanism involved in estrogen‐mediated cellular function within the oviduct remains unclear. In this study, we show in mouse models that ciliary length and beat frequency of the oviductal epithelial cells are regulated through estrogen receptor α (ESR1) but not estrogen receptor β (ESR2). Gene profiling indicated that transcripts in the WNT/ β‐catenin (WNT/CTNNB1) signaling pathway were regulated by estrogen in mouse oviduct, and inhibition of this pathway in a whole oviduct culture system resulted in a decreased embryo transport distance. However, selective ablation of CTNNB1 from the oviductal ciliated cells did not affect embryo transport, possibly because of a compensatory mechanism via intact CTNNB1 in the adjacent secretory cells. In summary, we demonstrated that disruption of estrogen signaling in oviductal epithelial cells alters ciliary function and impairs embryo transport. Therefore, our findings may provide a better understanding of etiology of the ectopic pregnancy that is associated with alteration of estrogen signals. —Li, S., O'Neill, S. R. S., Zhang, Y., Holtzman, M. J., Takemaru, K.‐I., Korach, K. S., Winuthayanon, W. Estrogen receptor α is required for oviductal transport of embryos. FASEB J . 31, 1595–1607 (2017) www.fasebj.org